Social Media Usage, Eating Habits and Nutritional Status of School-Going Adolescents: A Descriptive Study - Shinde, Nutan; Garg, Vandana (International Journal of Scientific Research in Biological Sciences, 2020)
Influence of social media on eating habits of adolescent children (increased number of meals taken other than home; consumption of junk foods in the forms of snacks and soft drinks) could increase their chances of developing health risks in adulthood such as obesity. Therefore, we aimed to assess the prevalent eating habits; physical activity, and use of social media among school-going adolescents. A cross-sectional descriptive study was carried out among 150 adolescents studying in a private school, located in the suburban area of Faridabad. Data related to social media usage, eating habits and physical activity was collected using self-administered questionnaires. The purposive sampling strategy was used to recruit students from classes eight to ten aged between 12-18 years. A total sample of 150 students comprised 63% boys and 37% girls. The mean age of the students was 14.2?1.12 years. There was a significant difference between the BMI of students who spent ≤ 3 hours and > 3 hours on social media as mean BMI was 18.13?2.64 and 19.59?3.94 respectively with the increase in time spent on social media. Frequent consumption of food items high in salt, sugar, and fat was also seen. Increased time spent on social media sites just for fun activity would be reducing the nutritional status of adolescents. Less intake of nutritious food might also cause micronutrient deficiency. We need to conduct more such studies to find the health effects of excess social media usage